Sulfide-polymer composite solid electrolyte, method for preparing the same, and solid-state battery

CN122992149APending Publication Date: 2026-10-27GAC AION NEW ENERGY AUTOMOBILE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510464363.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-14
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

[0023]由于采用上述制备方法制备得到的硫化物-聚合物复合固态电解质具有较高的离子电导率,应用于固态电池中,可有效提高固态电池的容量、首次库伦效率(以下简称首效)以及循环性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992149A_ABST
    Figure CN122992149A_ABST
Patent Text Reader

Abstract

The application provides a sulfide-polymer composite solid electrolyte and a preparation method and a solid-state battery thereof, and relates to the technical field of solid-state batteries. The preparation method comprises the following steps: dissolving a lithium salt, isocyanuric acid triglycidyl ester and an initiator in an ether monomer, and dispersing a sulfide solid electrolyte to obtain a mixed slurry; and coating the mixed slurry on the surface of a substrate, and obtaining the sulfide-polymer composite solid electrolyte after solidification. By mixing and solidifying the ether monomer, the isocyanuric acid triglycidyl ester and the sulfide solid electrolyte, the sulfide solid electrolyte is uniformly dispersed in the polymer, the introduction of the isocyanuric acid triglycidyl ester effectively improves the compatibility between the polymer monomer and the sulfide solid electrolyte, and the side reaction between the ether monomer and the sulfide solid electrolyte is inhibited, so that the ionic conductivity of the composite solid electrolyte is effectively improved, and the capacity, the initial efficiency and the cycle performance of the solid-state battery are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of solid-state battery technology, and in particular to a sulfide-polymer composite solid electrolyte, its preparation method, and a solid-state battery. Background Technology

[0002] In the field of solid electrolytes for solid-state batteries, due to the high ionic conductivity (10) of sulfides, -3 ~10 -2 Due to the advantages of sulfide-polymer composite solid electrolytes (S / cm) and the good processability of polymers, they have been extensively studied. Currently, the preparation method of sulfide-polymer composite solid electrolytes typically involves mixing polymers (such as polyethers, polyacrylonitrile, polyvinylidene fluoride, etc.), lithium salts (such as lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, etc.), sulfide solid electrolytes (such as LPSCl), and polar solvents (such as acetonitrile, DMF, etc.) to obtain a mixed slurry. This slurry is then coated onto a substrate, and the solvent is removed by baking to form the composite solid electrolyte. However, due to the poor compatibility between sulfide solid electrolytes and polymers, and the tendency for polar solvents to react with sulfide solid electrolytes, leading to their failure, the composite solid electrolytes prepared using the above methods often fail to effectively utilize the advantages of sulfide solid electrolytes, resulting in low ionic conductivity. Summary of the Invention

[0003] This application is made in view of the above-mentioned issues, and its purpose is to provide a sulfide-polymer composite solid electrolyte, a method for preparing the same, and a solid battery, with the aim of improving the ionic conductivity of the sulfide-polymer composite solid electrolyte.

[0004] The first aspect of this application provides a method for preparing a sulfide-polymer composite solid electrolyte, comprising the following steps:

[0005] Lithium salt, triglycidyl isocyanurate, and an initiator are dissolved in an ether monomer and a sulfide solid electrolyte is dispersed to obtain a mixed slurry. The mixed slurry is coated onto the surface of a substrate and cured to obtain a sulfide-polymer composite solid electrolyte.

[0006] In the above technical solution, by mixing and curing ether monomers, triglycidyl isocyanate, and sulfide solid electrolyte, the sulfide solid electrolyte can be uniformly dispersed in the cross-linked network structure formed by the polymerization of ether monomers and triglycidyl isocyanate. During the dispersion and curing process of the sulfide solid electrolyte, the interaction force between the carbonyl functional group in triglycidyl isocyanate and the sulfide solid electrolyte is greater than that between the ether oxygen functional group and the sulfide solid electrolyte. Furthermore, since the carbonyl functional group is relatively stable with the sulfide solid electrolyte, the electrophilic reaction between the ether oxygen functional group and the sulfide solid electrolyte is suppressed. This effectively improves the compatibility between the ether monomer and the sulfide solid electrolyte, thereby effectively increasing the ionic conductivity of the sulfide-polymer composite solid electrolyte.

[0007] In some embodiments, the mass ratio of the ether monomer, triglycidyl isocyanurate, and sulfide solid electrolyte is 1:(0.03-0.15):(0.2-1.6).

[0008] In the above technical solution, based on the good compatibility between ether monomers and sulfide solid electrolytes, by controlling the mass ratio of ether monomers, triglycidyl isocyanurate and sulfide solid electrolytes within the appropriate range, the mass proportion of sulfide solid electrolytes in the system is wide and uniformly dispersed. This allows more ions to be conducted through the sulfide solid electrolyte body or the sulfide-polymer interface as needed, which is beneficial to further improve the ionic conductivity of the sulfide-polymer composite solid electrolyte.

[0009] By controlling the amount of triglycidyl isocyanurate added within the above range, it can effectively suppress the side reactions between ether monomers and sulfide solid electrolytes. At the same time, it can control the degree of polymer crosslinking within a suitable range, thereby exhibiting high antioxidant capacity, adapting to a wider electrochemical window, and being less prone to oxidation and side reactions under a high voltage of 4.3V. Furthermore, it can control the crystallinity of the polymer within a suitable range, which is beneficial to further improve the ionic conductivity of the sulfide-polymer composite solid electrolyte.

[0010] In some embodiments, the ether monomer is a cyclic ether monomer; further, the ether monomer includes at least one selected from 1,3-dioxane, 1,3-dioxane, 1,3,5-trioxane, or tetrahydrofuran. These cyclic ether monomers have lower polarity than existing polar solvents (such as acetonitrile, DMF, etc.), resulting in weaker interactions with sulfide solid electrolytes. Adding triglycidyl isocyanate can effectively suppress side reactions between these cyclic ether monomers and sulfide solid electrolytes, preventing the decomposition or failure of the sulfide. Furthermore, the low-polarity ether monomers can disperse the sulfide solid electrolyte and exhibit good compatibility, allowing for uniform dispersion of the sulfide solid electrolyte in the system, forming a stable composite system, which helps to maximize the performance of the sulfide solid electrolyte.

[0011] In some embodiments, the sulfide solid electrolyte includes at least one of Li6PS5X, LiGePS, LiSiPS, or LiSnPS; wherein X includes at least one of F, Cl, Br, or I. These sulfide solid electrolytes all exhibit high ionic conductivity and readily form stable composite systems with polymers, which is beneficial for further improving the ionic conductivity of the sulfide-polymer composite solid electrolyte.

[0012] In some embodiments, the preparation method of the mixed slurry includes: adding lithium salt and triglycidyl isocyanate to an ether monomer, stirring to dissolve, then adding a sulfide solid electrolyte, stirring to disperse, and finally adding an initiator and stirring to dissolve. By using the ether monomer as a solvent to dissolve the lithium salt and triglycidyl isocyanate and uniformly disperse the sulfide solid electrolyte, the raw materials can be mixed more evenly, resulting in a stable and dispersed slurry. Furthermore, adding the initiator last can prevent premature polymerization, which would affect the uniformity of the dispersion of the sulfide solid electrolyte.

[0013] In some embodiments, the lithium salt includes at least one selected from lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorooxalateborate, or lithium dioxoborate. These lithium salts exhibit good stability in the composite system, which is beneficial for ion transport and can further improve the ionic conductivity of the sulfide-polymer composite solid electrolyte.

[0014] In some embodiments, the concentration of lithium salt in the ether monomer is 0.5 mol / L to 2 mol / L. By controlling the concentration of lithium salt within a suitable range, it is beneficial to ion transport within the sulfide-polymer composite solid electrolyte, and it can also help improve the interfacial properties between the sulfide-polymer composite solid electrolyte and the electrode, thereby improving ion transport at the interface.

[0015] In some embodiments, the initiator includes at least one of aluminum trifluoromethanesulfonate, stannous octoate, lithium iodide, lithium hexafluorophosphate, or lithium difluorooxalate borate.

[0016] In some embodiments, the concentration of the initiator in the ether monomer is 0.1 mol / L to 1 mol / L.

[0017] By controlling the type and concentration of the initiator within a suitable range, the curing reaction rate of the mixed slurry can be effectively improved, and the polymer can have a suitable degree of crosslinking and appropriate molecular chain length, thereby further improving the ionic conductivity of the sulfide-polymer composite solid electrolyte.

[0018] In some embodiments, the coating thickness of the mixed slurry on the substrate surface is 15 μm to 100 μm.

[0019] In some embodiments, the substrate includes aluminum foil, copper foil, or release film.

[0020] In some implementations, the curing temperature is 50°C to 80°C, and the curing time is 3 hours to 8 hours.

[0021] The second aspect of this application provides a sulfide-polymer composite solid electrolyte, which is prepared by the above-described preparation method.

[0022] A third aspect of this application provides a solid-state battery, including the sulfide-polymer composite solid electrolyte of the second aspect of this application.

[0023] Since the sulfide-polymer composite solid electrolyte prepared by the above method has high ionic conductivity, its application in solid-state batteries can effectively improve the capacity, first coulombic efficiency (hereinafter referred to as first efficiency), and cycle performance of solid-state batteries. Attached Figure Description

[0024] Figure 1 This is a process flow diagram of a method for preparing a sulfide-polymer composite solid electrolyte provided in this application.

[0025] Figure 2 These are comparison images of the mixed slurry in Example 1 of this application before and after curing; wherein, Figure 2 In the image, A represents the optical image of the mixed slurry before curing. Figure 2 B in the image is the optical image of the cured slurry.

[0026] Figure 3 These are comparison images of the mixed slurry in Comparative Example 1 of this application before and after curing; wherein, Figure 3 In the image, A represents the optical image of the mixed slurry before curing. Figure 3 B in the image is the optical image of the cured slurry.

[0027] Figure 4 XPS spectra of LPSCl in the mixed slurry of Example 1 and Comparative Example 1 of this application, and pure LPSCl powder.

[0028] Figure 5 The diagram shows the DFT simulation calculation of the PS bond energy of LPSCl in the mixed slurry of Example 1 and Comparative Example 1 of this application.

[0029] Figure 6 The graphs show the cycle capacity curves of the solid-state batteries in Examples 1-4 and Comparative Example 1 of this application. Detailed Implementation

[0030] The following detailed description, with appropriate reference to the accompanying drawings, discloses the sulfide-polymer composite solid electrolyte, its preparation method, and embodiments of the solid-state battery. However, unnecessary details may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of essentially the same structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided for the purpose of enabling those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.

[0031] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of the particular range. The range defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range.

[0032] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions. Unless otherwise specified, all technical features and optional technical features of this application can be combined to form new technical solutions. Unless otherwise specified, all steps of this application can be performed sequentially or randomly, preferably sequentially.

[0033] Currently, the preparation method of sulfide-polymer composite solid electrolytes usually involves mixing polymers (such as polyether, polyacrylonitrile, polyvinylidene fluoride, etc.), lithium salts (such as lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethyl)sulfonyl)imide, sulfide solid electrolytes (such as LPSCl), and polar solvents (such as acetonitrile, DMF, etc.) to obtain a mixed slurry. The mixed slurry is then coated onto a substrate and baked to remove the solvent, thus forming the sulfide-polymer composite solid electrolyte.

[0034] However, the above preparation methods have the following problems: (1) The compatibility between sulfide solid electrolytes and polymers is poor, making it difficult to fully utilize the ionic conductivity advantage of sulfide solid electrolytes; (2) Polar solvents are usually added to the mixed slurry system. The polar functional groups on the polar solvents will attack the sulfide electrolytes through nucleophilic attacks, resulting in side reactions and causing the sulfide electrolytes to fail; (3) Sulfide-polymer composite solid electrolytes usually transport ions through the movement of polymer molecular chain segments. The polymer itself has low ionic conductivity (~10). -5 Due to the uneven dispersion of the sulfide inorganic electrolyte within the polymer network structure (S / cm), the crystallinity of the polymer cannot be effectively reduced, and the ionic conductivity advantage of the sulfide solid electrolyte cannot be fully utilized. Therefore, the ionic conductivity of the sulfide-polymer composite solid electrolyte prepared by the above method remains low.

[0035] Based on this, this application proposes a method for preparing a sulfide-polymer composite solid electrolyte. The method involves mixing and solidifying an ether monomer, triglycidyl isocyanate, and a sulfide solid electrolyte. The sulfide solid electrolyte is uniformly dispersed within the cross-linked network structure formed by the polymerization of the ether monomer and triglycidyl isocyanate. During the dispersion and solidification process of the sulfide solid electrolyte, the interaction force between the carbonyl functional group in the triglycidyl isocyanate and the sulfide solid electrolyte is greater than that between the ether oxygen functional group and the sulfide solid electrolyte. Furthermore, because the carbonyl functional group is more stable with the sulfide solid electrolyte, it inhibits the electrophilic reaction between the ether oxygen functional group and the sulfide solid electrolyte. This effectively improves the compatibility between the ether monomer and the sulfide solid electrolyte, thereby effectively increasing the ionic conductivity of the sulfide-polymer composite solid electrolyte.

[0036] The present application is further illustrated below with reference to embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the present application.

[0037] Figure 1 This is a process flow diagram of a method for preparing a sulfide-polymer composite solid electrolyte provided in this application. Please refer to [link / reference]. Figure 1 The preparation method includes the following steps:

[0038] S10: Dissolve lithium salt, triglycidyl isocyanate and initiator in ether monomers, and disperse sulfide solid electrolyte to obtain a mixed slurry.

[0039] In some embodiments, the ether monomer is a cyclic ether monomer.

[0040] Furthermore, the ether monomers include at least one of 1,3-dioxopentane (DOL), 1,3-dioxane (DOX), 1,3,5-trioxane (TXE), and tetrahydrofuran (THF).

[0041] "Ether monomers" refer to organic compounds that contain ether bonds (-O-) and can form polymers through polymerization. "Cyclic ether monomers" are organic compounds that not only contain ether bonds but also have a cyclic structure, and can form polymers through ring-opening polymerization.

[0042] In some embodiments, the sulfide solid electrolyte includes at least one of Li6PS5X, LiGePS, LiSiPS, or LiSnPS; wherein X includes at least one of F, Cl, Br, or I.

[0043] In some embodiments, the mass ratio of ether monomer, triglycidyl isocyanate (TGIC), and sulfide solid electrolyte is 1:(0.03–0.15):(0.2–1.6).

[0044] Furthermore, the mass ratio of the ether monomer, triglycidyl isocyanurate, and sulfide solid electrolyte is 1:(0.05–0.1):(0.6–1.2).

[0045] As an example, the mass ratio of ether monomers, triglycidyl isocyanurate, and sulfide solid electrolyte is 1:0.03:0.2, 1:0.05:0.6, 1:0.06:1, 1:0.08:1.2, 1:0.09:0.8, 1:0.1:0.6, 1:0.15:1.6, etc.

[0046] In some embodiments, step S10 includes: adding lithium salt and triglycidyl isocyanurate to the ether monomer, stirring to dissolve, adding sulfide solid electrolyte, stirring to disperse, and finally adding initiator and stirring to dissolve.

[0047] In some embodiments, the lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium trifluoromethanesulfonate (LiOTf), lithium bis(trifluoromethanesulfonylimide) (LiTFSI), lithium bis(fluorosulfonylimide) (LiFSI), lithium difluorooxalate borate (LiODFB), or lithium dioxoborate (LiBOB).

[0048] In some embodiments, the concentration of lithium salt in the ether monomer is 0.5 mol / L to 2 mol / L.

[0049] Furthermore, the concentration of lithium salt in the ether monomer is 0.8 mol / L to 1.2 mol / L.

[0050] For example, the concentrations of lithium salts in ether monomers are 0.5 mol / L, 0.8 mol / L, 1 mol / L, 1.2 mol / L, 1.5 mol / L, 2 mol / L, etc.

[0051] In some embodiments, the initiator includes at least one of aluminum trifluoromethanesulfonate (Al(OTf)3), stannous octoate (Sn(Oct)2), lithium iodide (LiI), lithium hexafluorophosphate (LiPF6), or lithium difluorooxalate borate (LiDFOB).

[0052] In some embodiments, the concentration of the initiator in the ether monomer is 0.1 mol / L to 1 mol / L.

[0053] Furthermore, the concentration of the initiator in the ether monomer is 0.3 mol / L to 0.8 mol / L.

[0054] As an example, the concentrations of the initiator in the ether monomers are 0.1 mol / L, 0.3 mol / L, 0.5 mol / L, 0.6 mol / L, 0.8 mol / L, and 1 mol / L.

[0055] S20: The mixed slurry is coated onto the substrate surface and cured to obtain a sulfide-polymer composite solid electrolyte.

[0056] In some embodiments, the coating thickness of the mixed slurry on the substrate surface is 15 μm to 100 μm. As an example, the coating thickness of the mixed slurry on the substrate surface is 15 μm, 30 μm, 50 μm, 60 μm, 80 μm, 100 μm, etc.

[0057] In some embodiments, the substrate includes aluminum foil, copper foil, or release film.

[0058] In some embodiments, the curing method is heat curing, with a curing temperature of 50°C to 80°C and a curing time of 3 hours to 8 hours. As examples, the curing temperature is 50°C, 60°C, 70°C, or 80°C, and the curing time is 3 hours, 4 hours, 5 hours, 7 hours, or 8 hours, etc.

[0059] In addition, this application also provides a sulfide-polymer composite solid electrolyte prepared by the above preparation method, which has an ionic conductivity of ≥0.50 mS / cm.

[0060] In addition, this application also provides a solid-state battery, including a positive electrode, a negative electrode, and the above-mentioned sulfide-polymer composite solid electrolyte.

[0061] The aforementioned sulfide-polymer composite solid electrolyte is in membrane form and can be directly disposed between the positive and negative electrodes to form a solid-state battery. Due to its high ionic conductivity, the sulfide-polymer composite solid electrolyte can effectively improve the first-charge specific capacity, first-discharge specific capacity, first-cycle efficiency, and cycle capacity retention of the solid-state battery.

[0062] Example

[0063] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.

[0064] Example 1

[0065] This embodiment provides a sulfide-polymer composite solid electrolyte, the preparation method of which includes the following steps:

[0066] (1) Take 100g of ether monomer (1,3-dioxapentane, DOL), add lithium salt (lithium bis(trifluoromethanesulfonyl)imide, LiTFSI) and stir to dissolve, so that the concentration of lithium salt in ether monomer is 1mol / L; then add 6.5g of triglycidyl isocyanate (TGIC), stir to dissolve, then add 100g of sulfide solid electrolyte (LPSCl) and stir until stable dispersion, finally add initiator (lithium difluorooxalate borate, LiDFOB), the concentration of initiator is 0.6mol / L, stir until completely dissolved, and obtain a stable dispersion mixed slurry.

[0067] (2) The mixed slurry in step (1) is applied to the surface of the release film with a coating thickness of 50 μm, and then placed in an oven at 60°C for 7 hours to cure and form a sulfide-polymer composite solid electrolyte.

[0068] Example 2

[0069] This embodiment provides a sulfide-polymer composite solid electrolyte, the preparation method of which includes the following steps:

[0070] (1) Take 100g of ether monomer (1,3-dioxapentane, DOL), add lithium salt (lithium bis(trifluoromethanesulfonyl)imide, LiTFSI) and stir until completely dissolved, so that the concentration of lithium salt in ether monomer is 0.8mol / L; then add 8g of triglycidyl isocyanate (TGIC), stir until completely dissolved, then add 120g of sulfide solid electrolyte (LPSCl) and stir until uniformly dispersed, and finally add initiator (lithium difluorooxalate borate, LiDFOB), the concentration of initiator is 0.8mol / L, stir until completely dissolved, and obtain a stable and dispersed mixed slurry.

[0071] (2) The mixed slurry in step (1) is applied to the surface of the release film with a coating thickness of 80 μm, and then placed in an oven at 80°C for 4 hours to heat and cure, forming a sulfide-polymer composite solid electrolyte.

[0072] Example 3

[0073] This embodiment provides a sulfide-polymer composite solid electrolyte, the preparation method of which includes the following steps:

[0074] (1) Take 100g of ether monomer (1,3-dioxapentane, DOL), add lithium salt (lithium bis(trifluoromethanesulfonyl)imide, LiTFSI) and stir until completely dissolved, so that the concentration of lithium salt in ether monomer is 1.1mol / L; then add 9g of triglycidyl isocyanate (TGIC), stir until completely dissolved, then add 80g of sulfide solid electrolyte (LPSCl) and stir until uniformly dispersed, and finally add initiator (lithium difluorooxalate borate, LiDFOB) with a concentration of 0.5mol / L, stir until completely dissolved, and obtain a stable and dispersed mixed slurry.

[0075] (2) The mixed slurry in step (1) is applied to the surface of the release film with a coating thickness of 60 μm, and then placed in a 70℃ oven for heating and curing for 5 h to form a sulfide-polymer composite solid electrolyte.

[0076] Example 4

[0077] This embodiment provides a sulfide-polymer composite solid electrolyte, the preparation method of which includes the following steps:

[0078] (1) Take 100g of ether monomer (1,3-dioxapentane, DOL), add lithium salt (lithium bis(trifluoromethanesulfonyl)imide, LiTFSI) and stir until completely dissolved, so that the concentration of lithium salt in ether monomer is 1.2mol / L; then add 10g of triglycidyl isocyanate (TGIC), stir until completely dissolved, then add 100g of sulfide solid electrolyte (LPSCl) and stir until uniformly dispersed, and finally add initiator (lithium difluorooxalate borate, LiDFOB), the concentration of initiator is 0.3mol / L, stir until completely dissolved, and obtain a stable and dispersed mixed slurry.

[0079] (2) The mixed slurry in step (1) is applied to the surface of the release film with a coating thickness of 30 μm, and then placed in a 50°C oven for heating and curing for 8 hours to form a sulfide-polymer composite solid electrolyte.

[0080] Comparative Example 1

[0081] This comparative example provides a sulfide-polymer composite solid electrolyte, the preparation method of which differs from that of Example 1 in that triglycidyl isocyanate (TGIC) is not added in step (1).

[0082] The preparation parameters of the sulfide-polymer composite solid electrolyte in Examples 1 to 4 and Comparative Example 1 are shown in Table 1.

[0083] Table 1. Some preparation parameters of the sulfide-polymer composite solid electrolyte in the examples and comparative examples.

[0084]

[0085] Experimental Example 1

[0086] The appearance and properties of the mixed slurry in Example 1 and Comparative Example 1 were tested before and after curing.

[0087] Figure 2 These are comparison images of the mixed slurry in Example 1 of this application before and after curing; wherein, Figure 2 In the image, A represents the optical image of the mixed slurry before curing. Figure 2 B in the image is the optical image of the cured slurry. Figure 3 These are comparison images of the mixed slurry in Comparative Example 1 of this application before and after curing; wherein, Figure 3 In the image, A represents the optical image of the mixed slurry before curing. Figure 3 B in the image represents the optical image of the cured mixed slurry. Further integration... Figure 2 and Figure 3 It can be seen that the color of the mixed slurry in Example 1 did not change significantly before and after curing, indicating that the introduction of triglycidyl isocyanate (TGIC) effectively inhibited the reaction between the polar ether oxygen functional groups in the ether monomer and the sulfide solid electrolyte. In contrast, in Comparative Example 1, without the addition of triglycidyl isocyanate (TGIC), the color of the mixed slurry changed from white to a distinct brown before and after curing, and the color further deepened after curing, indicating that the ether monomer and the sulfide solid electrolyte were incompatible and side reactions occurred.

[0088] Figure 4 XPS spectra of LPSCl in the mixed slurry of Example 1 and Comparative Example 1, and pure LPSCl powder. In Example 1 and Comparative Example 1, the LPSCl was obtained by vacuum filtration and vacuum drying of the mixed slurry before curing. Figure 4 As can be seen from the data, the characteristic peaks of the sulfide solid electrolyte (LPSCl) in Example 1 are basically consistent with those of pure LPSCl powder. However, the characteristic peak positions and peak intensities of the sulfide solid electrolyte (LPSCl) in Comparative Example 1 have changed significantly. This further indicates that the ether monomer and the sulfide solid electrolyte in Comparative Example 1 are incompatible and undergo side reactions, resulting in changes in the structure of the sulfide solid electrolyte (LPSCl). Figure 5 This is a DFT simulation diagram of the PS bond energy of LPSCl in the mixed slurry of Example 1 and Comparative Example 1 of this application. The PS bond energy of LPSCl was calculated based on density functional theory (DFT). Figure 5It can be seen that the PS bond energy of LPSCl in Example 1 is 3.5, while the PS bond energy of LPSCl in Comparative Example 1 is 3.2. The larger PS bond energy of LPSCl in Example 1 indicates that the polar functional group of the ether monomer (DOL) is more difficult to react with the sulfide solid electrolyte (LPSCl), further demonstrating that the introduction of TGIC inhibits the side reactions between the ether monomer (DOL) and the sulfide solid electrolyte (LPSCl).

[0089] Experimental Example 2

[0090] Using the sulfide-polymer composite solid electrolytes prepared in Examples 1-4 and Comparative Example 1 as solid electrolyte membranes, solid-state batteries were fabricated, and their electrochemical performance was tested. The test results are shown in Table 2. Among them, the LiNi in the positive electrode... 0.8 Co 0.1 Mn 0.1 The mass ratio of O2 (NCM811), Super P, and polyvinylidene fluoride (PVDF) is 8:1:1, and the diameter of the positive electrode is 12 mm; the diameter of the solid electrolyte membrane (i.e., the above-mentioned sulfide-polymer composite solid electrolyte) is 19 mm, and the diameter of the lithium sheet (i.e., the negative electrode) is 15.6 mm.

[0091] 1. Sulfide-polymer composite solid electrolyte

[0092] Ionic conductivity: Electrochemical impedance spectroscopy was performed using an electrochemical workstation with a scanning frequency of 10 mHz to 100 kHz and an amplitude of 10 mV to obtain the electrochemical impedance spectrum. The bulk resistance R of the electrolyte membrane can then be obtained. Using the formula σ = L / (R × S), where σ is the ionic conductivity, L is the thickness of the sulfide-polymer composite solid electrolyte membrane, R is the bulk resistance, and S is the area of ​​the sulfide-polymer composite solid electrolyte membrane, the ionic conductivity of the sulfide-polymer composite solid electrolyte can be calculated.

[0093] 2. Solid-state batteries

[0094] (1) Initial charge specific capacity: Under normal temperature (25℃) conditions, the initial charge specific capacity is obtained by constant current charging at 0.1C to the cutoff voltage of 4.3V.

[0095] (2) First discharge specific capacity: Under normal temperature environment (25℃), the fully charged battery is discharged at a constant current of 0.1C to the cutoff voltage of 2.5V to obtain the first discharge specific capacity.

[0096] (3) First-time efficiency: First-time efficiency = First discharge specific capacity / First charge specific capacity × 100%.

[0097] (4) Cycle capacity retention: At room temperature (25℃), the battery is charged at a current of 0.1C to the charging cutoff voltage of 4.3V, then switched to constant voltage charging to the cutoff current of 0.05C, allowed to stand for 0.5h, and then discharged at a current of 0.1C to the cutoff voltage of 2.5V, allowed to stand for 0.5h, and then entered the next charge-discharge cycle. This process is repeated for a total of 50 charge-discharge cycles. Cycle capacity retention = (discharge specific capacity of the 50th cycle / discharge specific capacity of the first cycle) × 100%.

[0098] Table 2 shows the performance of sulfide-polymer composite solid electrolytes and solid batteries in the examples and comparative examples.

[0099]

[0100] As can be seen from Tables 1 and 2, compared to Comparative Example 1, the sulfide-polymer composite solid electrolytes prepared in Examples 1 to 4 by adding triglycidyl isocyanate (TGIC) and mixing and curing it with ether monomers and sulfide solid electrolytes exhibit higher ionic conductivity (≥0.50 mS / cm), and the ionic conductivity does not decrease significantly before and after curing. The corresponding solid-state batteries prepared have higher initial charge specific capacity, initial discharge specific capacity, and higher initial efficiency and cycle capacity retention. The initial charge specific capacity at 0.1C is ≥220 mAh / g, the initial discharge specific capacity is ≥180 mAh / g, the initial efficiency is ≥80%, and the capacity retention after 50 cycles at 0.1C is ≥90%.

[0101] Figure 6 The following are cycle capacity curves for Examples 1-4 and Comparative Example 1 of this application. Figure 6 As can be seen from the data, the discharge specific capacity of the solid-state batteries prepared in Examples 1 to 4 is significantly higher than that of Comparative Example 1 during the cycling process.

[0102] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. A method for preparing a sulfide-polymer composite solid electrolyte, characterized in that, Includes the following steps: Lithium salt, triglycidyl isocyanate and initiator are dissolved in ether monomers, and sulfide solid electrolyte is dispersed to obtain a mixed slurry; The mixed slurry is coated onto the substrate surface and cured to obtain a sulfide-polymer composite solid electrolyte.

2. The preparation method according to claim 1, characterized in that, The mass ratio of the ether monomer, the triglycidyl isocyanurate, and the sulfide solid electrolyte is 1:(0.03-0.15):(0.2-1.6).

3. The preparation method according to claim 1, characterized in that, The ether monomers are cyclic ether monomers; Optionally, the ether monomer includes at least one of 1,3-dioxane, 1,3-dioxane, 1,3,5-trioxane, or tetrahydrofuran.

4. The preparation method according to claim 1, characterized in that, The sulfide solid electrolyte includes at least one of Li6PS5X, LiGePS, LiSiPS, or LiSnPS; Wherein, X includes at least one of F, Cl, Br or I.

5. The preparation method according to claim 1, characterized in that, The method for preparing the mixed slurry includes: The lithium salt and the triglycidyl isocyanurate are added to the ether monomer and stirred to dissolve. Then the sulfide solid electrolyte is added and stirred to disperse. Finally, the initiator is added and stirred to dissolve.

6. The preparation method according to claim 5, characterized in that, The concentration of the lithium salt in the ether monomer is 0.5 mol / L to 2 mol / L; And / or, the concentration of the initiator in the ether monomer is 0.1 mol / L to 1 mol / L.

7. The preparation method according to claim 5, characterized in that, The lithium salt includes at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorooxalateborate, or lithium dioxoborate. And / or, the initiator includes at least one of aluminum trifluoromethanesulfonate, stannous octoate, lithium iodide, lithium hexafluorophosphate, or lithium difluorooxalate borate.

8. The preparation method according to claim 1, characterized in that, The curing temperature is 50℃~80℃, and the time is 3h~8h.

9. A sulfide-polymer composite solid electrolyte, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 8.

10. A solid-state battery, characterized in that, It includes a positive electrode, a negative electrode, and a sulfide-polymer composite solid electrolyte as described in claim 9.